ESTIMATING THE ENGEL CURVES FOR HOUSEHOLD EXPENDITURES IN JORDAN FROM 2010 TO 2011 - Al-Habashneh, Fedel; Al-Majali, Khalid (European Scientific Journal, ESJ, 2014)
This present study aims at estimating the Engel curves for household expenditures using data of household expenditures and income survey of Jordan for the year 2010. In order to achieve the above objective, six functional forms have been formulated and estimated. The data was grouped into nine commodity groups from the raw data which covers 13866 households from urban and rural areas. The main findings of the study are 1. The family size does not affect the demand for the Vice, Housing, Transportation and Health Commodity groups. On the other hand, the family size for the other groups is significantly different from zero which suggests that family size affect the demand for these commodity groups. 2. The family size does not affect per-capita consumption of these commodity groups. The t-test indicates that there are economies of scale only for food. 3. The consumption pattern for clothing, housing, personal care and miscellaneous commodity group, are not the same in urban and in rural areas.